2021
DOI: 10.1177/21501327211041846
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Experiences of “Long COVID” in the Community and Recommendations for Improving Services: A Quality Improvement Survey

Abstract: Introduction: “Long COVID” is a multisystem disease that lasts for 4 or more weeks following initial symptoms of COVID-19. In the UK, at least 10% of patient report symptoms at 12 weeks following a positive COVID-19 test. The aims of this quality improvement survey were to explore patients’ acute and post-acute “long” COVID-19 symptoms, their experiences of community services and their recommendations for improving these services. Methods: Seventy patients diagnosed with COVID were randomly selected from 2 lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…In contrast, a British study reported how COVID-19 participants felt distrusted by healthcare professionals ( 18 ). Moreover, recent qualitative studies showed that post-COVID patients felt a lack of support and were dismissed by health professionals when addressing their symptoms ( 14 , 17 , 22 ). In addition, the current participants emphasized that they wanted to feel secure and cared for, which is in line with previous research that highlighted the participants’ needs to be acknowledged and believed was crucial for their recovery ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a British study reported how COVID-19 participants felt distrusted by healthcare professionals ( 18 ). Moreover, recent qualitative studies showed that post-COVID patients felt a lack of support and were dismissed by health professionals when addressing their symptoms ( 14 , 17 , 22 ). In addition, the current participants emphasized that they wanted to feel secure and cared for, which is in line with previous research that highlighted the participants’ needs to be acknowledged and believed was crucial for their recovery ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, participants felt content with going back slowly at a steady pace, although they did worry about whether they would be able to go back to work full-time. It seems that other qualitative studies present more anxiety concerning the return to work process (15,17,25). This applies both to concerns about working part-time and to worries concerning whether participants would receive extended sick-leave (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carfì et al described that two months after discharge from the ICU, about 44% of COVID-19 patients showed a worsened quality of life, with more than 50% of them showing fatigue [60]. In a quality improvement survey, Razai found that post-acute COVID-19 patients self-reported neurocognitive difficulties, such as a lack of memory and concentration, headache and "brain fog" [61].…”
Section: Covid-19mentioning
confidence: 99%
“…Further, we retrieved and examined the full texts of those citations and excluded 21 that did not meet all criteria. Finally, 15 articles representing 12 studies were included in this qualitative systematic review and summarized in Table 2 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Literature Retrievalmentioning
confidence: 99%